The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1074/jbc.273.3.1568
|View full text |Cite
|
Sign up to set email alerts
|

Physical Interaction between Epidermal Growth Factor Receptor and DNA-dependent Protein Kinase in Mammalian Cells

Abstract: Binding of extracellular ligands to epidermal growth factor receptors (EGFR) activate signal transduction pathways associated with cell proliferation, and these events are inhibited by monoclonal antibodies against EGFR. Since efficient DNA repair in actively growing cells may require growth factor signaling, it was of interest to explore any linkage between EGFR-mediated signaling and DNA-dependent protein kinase (DNA-PK), an enzyme believed to be involved in repairing double strand breaks and V(D)J recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
0
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(131 citation statements)
references
References 35 publications
(44 reference statements)
3
123
0
5
Order By: Relevance
“…DNA damage is modulated by metabolic DNA repair processes. Interestingly, Bandyopadhyay et al (1998) have shown that EGFR-mediated signalling may control the activity of DNA-PK, an enzyme directly involved in DNA damage repair; more For each combination sequence of ZD1839 and radiation, the dose-effect curve of the combination was compared with the dose-effect curves of ZD1839 alone and radiation alone. Radiation dose ranged from 0.5 to 10 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage is modulated by metabolic DNA repair processes. Interestingly, Bandyopadhyay et al (1998) have shown that EGFR-mediated signalling may control the activity of DNA-PK, an enzyme directly involved in DNA damage repair; more For each combination sequence of ZD1839 and radiation, the dose-effect curve of the combination was compared with the dose-effect curves of ZD1839 alone and radiation alone. Radiation dose ranged from 0.5 to 10 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…The lysates were centrifuged in an Eppendorf centrifuge at 48C for 15 min. Cell lysates containing equal amounts of protein were resolved on a 10% SDS-polyacrylamide gel, transferred to nitrocellulose, and probed with the appropriate antibodies, using an ECL method or alkaline phosphatase-based color reaction method (Bandyopadhyay et al, 1998).…”
Section: Cell Extracts Immunoblotting and Immunoprecipitationmentioning
confidence: 99%
“…Cellular localization of Bax and p53 was determined using indirect immuno¯uorescence (Martin et al, 1987) with some modi®cations (Bandyopadhyay et al, 1998). Brie¯y, cells grown on glass coverslips were ®xed in methanol at 7208C for 10 min.…”
Section: Immuno¯uorescence and Confocal Studiesmentioning
confidence: 99%